COMPARATIVE STUDY OF PROLONGED FLUORIDE ION RELEASE IN CONTEMPORARY DENTAL ENAMEL SEALANTS - Noenko, Igor; Karpchuk, Liudmyla; Gurando, Vyacheslav; Maryan-Yovbak, Viktoria; Kulish, Andrii; Mochalov, Iurii (Eastern Ukrainian Medical Journal, 2024)
The objective of the study was to investigate the amount of long-term fluoride ion release from three materials (sealants) – “Fissurit FX”, “Clinpro™Sealant” and “Jen-Fissufil” in laboratory condition.Materials and methods: 4 standard samples from three modern photocomposite sealants for tooth enamel (“Fissurit FX” (VOCO), “Clinpro™Sealant” (3M™ ESPE™) and “Jen-Fissufil” (Jendental Ukraine LLC)) were polymerized according to instructions of producer and were placed in deionized water in plastic tubes. The conditions for manufacturing the samples were standardized, with the air temperature in the laboratory maintained at 22.0 ± 1.0 °C and the relative humidity at 50.0 ± 5.0%. These conditions comply with ISO 7489 standards. An amount of fluoride ions was studied using the electronic ionometer on 1st, 2nd, 3rd, 8th, 15th, 22nd and 32nd day of exposition in the deionized water tacked from plastic tube. Throughout the study duration, the tubes containing the samples were stored in a thermostat at a temperature of 37.00 ± 0.50°CResults: The all three enamel sealants selected for the study released fluoride ions for an extended period after polymerization, up to 30 days. The highest level of fluoride ion emission in distilled water occured on the next day after polymerization. This phenomenon can be attributed to the ongoing polymerization-depolymerization reactions within the material itself (composite conversion). “Fissurit FX” samples showed the highest F- release: 4.80 µg/cm² – day 1, and stabilized at 0.45 µg/cm² by day 14. Day 14 to 30 – from 0.13 to 0.17 µg/cm². “Jen-Fissufil” released 3.54 µg/cm² on 1st day, 0.74 µg/cm² on 7th, and 0.26 – 0.44 µg/cm² afterwards. “Clinpro™Sealant” – 1.84 µg/cm² of F- on 1st day, 0.58 on 2nd, 0.53 µg/cm² on 3rd. From 21st day – from 0.20 to 0.21 µg/cm². Comparison of the levels of fluoride ion release revealed a consistent pattern of element release within a month after polymerization for all materials: “Jen-Fissufil” exhibited the highest release, followed by “Clinpro™Sealant” and “Fissurit FX” with the lowest release. This trend was consistent throughout the month, except for the first day when “Fissurit FX” exhibited the highest release of fluoride ions.Conclusions: The enamel dental composite sealants “Fissurit FX”, “Clinpro™Sealant” and “Jen-Fissufil” are capable of emitting fluoride ions after use on enamel. The highest level of emission in distilled water occurs 24 hrs after polymerization, the process lasts more than 30 days in less amounts.